Sistem Informasi Manajemen Terintegrasi untuk Optimalisasi Kinerja pada Fajar Zahra Laundry - Ikhwan Anshori; Nori Sahrun; Sularno Sularno (Journal Of Informatics And Busisnes, 2026)
The rapid development of information technology offers significant opportunities for small and medium-sized enterprises (SMEs) to enhance service quality and operational efficiency through digital systems. Fajar Zahra Laundry, a kilo-based laundry business located in Bagan Siapi-api, previously relied on manual methods for recording customer data and transactions. This approach led to various issues such as data loss, recording errors, and delays in generating financial reports. To address these challenges, a web-based laundry management system was designed and developed using PHP, the CodeIgniter framework, and a MySQL database.The system was built using the System Development Life Cycle (SDLC) with the waterfall model, covering stages such as analysis, design, implementation, testing, and maintenance. Key features of the system include customer data management, transaction processing based on service types, laundry status tracking, and automated daily and monthly financial reporting. Additionally, the system includes user authentication with login and logout features to ensure data security.The implementation results show that the system significantly improves operational efficiency, reduces manual workloads, and helps the business owner monitor the laundry’s financial and customer data in real-time. With this information system, Fajar Zahra Laundry is expected to provide more professional and competitive services in the digital era.